YAP regulates the liver size during the fasting-refeeding transition in mice - Xuan Li; Shicheng Fan; Chenghui Cai; Yue Gao; Xinhui Wang; Yifei Zhang; Hangfei Liang; Huilin Li; Jie Yang; Min Huang; Huichang Bi (Elsevier, 2023)
Liver is the central hub regulating energy metabolism during feeding-fasting transition. Evidence suggests that fasting and refeeding induce dynamic changes in liver size, but the underlying mechanisms remain unclear. Yes-associated protein (YAP) is a key regulator of organ size. This study aims to explore the role of YAP in fasting- and refeeding-induced changes in liver size. Here, fasting significantly reduced liver size, which was recovered to the normal level after refeeding. Moreover, hepatocyte size was decreased and hepatocyte proliferation was inhibited after fasting. Conversely, refeeding promoted hepatocyte enlargement and proliferation compared to fasted state. Mechanistically, fasting or refeeding regulated the expression of YAP and its downstream targets, as well as the proliferation-related protein cyclin D1 (CCND1). Furthermore, fasting significantly reduced the liver size in AAV-control mice, which was mitigated in AAV Yap (5SA) mice. Yap overexpression also prevented the effect of fasting on hepatocyte size and proliferation. Besides, the recovery of liver size after refeeding was delayed in AAV Yap shRNA mice. Yap knockdown attenuated refeeding-induced hepatocyte enlargement and proliferation. In summary, this study demonstrated that YAP plays an important role in dynamic changes of liver size during fasting-refeeding transition, which provides new evidence for YAP in regulating liver size under energy stress.